Building Mathematical Concepts Through Traditional Games to Develop Counting Skills for Early Childhood - Wulansari, Widi; Dwiyanti, Linda (Universitas Pendidikan Ganesha, 2021)
In recent years, fun learning methods have almost disappeared from school classrooms. In addition, there is a reduction in active and creative playtime so that students feel bored. This study aims to build (C5) simple mathematical concepts with the traditional game Dakon and Snakes and Ladders in developing numeracy skills in children with high and low order thinking abilities. The type of research used is quasi-experimental research (quasi-experimental) with a 2x2 factorial design. The subjects in this study were 60 children in group B. The data collection techniques used in this study were tests and observations. The instrument used is a test question, and the observation sheet uses five indicators to measure the ability to count ata analysis using Two Way ANOVA test. This research aims to build a simple mathematical concept with traditional dakon games to develop numeracy skills in children with higher-order thinking skills, which gives better results than the traditional snake and ladder game with a Mean Difference value of 1.533 and a Significance value of 0.0001. Building simple mathematical concepts with traditional dakon games to develop numeracy skills in children with low-level thinking abilities gave better results than the traditional snake and ladder game with a Mean Difference value of 2.867 and a Significance value of 0.0001. Thus, it can be concluded that the traditional dakon game is very well used to build simple mathematical concepts, especially numeracy skills.